Effect of Polyunsaturated Fatty Acids on Hepatic Injury in Rats With Obstructive Jaundice (Annals of Medical Research, 2021)
None
Keywords: Biliary obstruction, Polyunsaturated phophatidylcholine, Pro-inflammatory cytokines